The Nationwide assessment for the Needs and Pathways for integration of Climate Smart Agriculture (CSA) – Climate Information Services (CIS) into the Curricula of Zambian Higher Education Institutions - Chinene, VRN; Phiri, E; Mweetwa, AM; Yengwe, J; Sinda, MC; Lungu, ON; Kaluba, P (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report presents results from a survey conducted to understand the extent to which HEIs in Zambia have integrated CSA-CIS in the curricula and identify the needs & possible approaches for integrating the CSA and CIS in the HEI programmes. Climate-Smart Agriculture (CSA) is an approach for transforming and reorienting agricultural systems to support food security under the new realities of climate change. Climate Iinformation Services (CIS) involve collating, analysing, packaging up and distributing climate data on variables such as temperature, rainfall, wind, soil moisture and extreme weather conditions and extreme weather indicators.